Adaptation to Climate Change in Water Management, Agrobiodiversity and Forestry with Special Reference to Nepal - Shrestha, Ujjwal T (The Initiation, 2010)
Analysis of recent climatic trends reveals a significant sign of warming in recent decades which has been more pronounced at higher altitudes. Climate change scenarios for Nepal show considerable convergence on continued warming, Warming trends have already had significant impacts in the Nepal Himalayas -most significantly in terms of glacier retreat such as increase in size and volume of glacial lakes, making them more prone to glacial lake outburst flooding (GLOF). This contributes to enhanced variability of river flows. The indepth analysis of water resources in Nepal identifies two critical impacts of climate change- GLOFs and variability of river runoff- both of which pose significant impacts not only on hydropower, but also on rural livelihoods and agriculture. The range of practices that can be used to adapt the climate change is diverse, and includes changes in behavior, structural policy based responses, technological or managerial responses. Key Words: Adaptation, Climate change, Forestry, Agrobiodiversity, GLOF DOI: 10.3126/init.v2i1.2532 The Initiation Vol.2(1) 2008 pp113-120